Pembuatan Website E-Commerce Penjualan Barang Untuk Perusahaan PT. X dengan Fitur Data Mining Generalize Sequential Pattern - Tansil, Davin Ardian; Budhi, Gregorius Satia; Rostianingsih, Silvia (Jurnal Infra, 2016)
PT. X is a company that sell cars and carâs spare parts by retail that use brick and mortar as base. PT. X want to make e-commerce website with hope that the website will help them expanding their market area for facing the rivalry with similar companies.The website poses online market feature that will help the users make their purchase and tracking their transaction they have done, users are divided into two category users and admin, admin are the PT. X promoting and selling their goods, while the users are the one who purchase through the website. This web is scripted using PHP, Ajax, and JavaScript, and user MySQL for creating the database. The development is done using notepad++ software.The data mining feature is based on generalize sequential pattern algorithm, where this feature is used to analyze the customers purchase behaviors and patterns by finding the connection between sold items based on time. Data is processed using the algorithm resulting frequent item sets that will turn into association rules in form of generalize sequential pattern table.